Physical health problems among the geriatric population in Perambalur municipality, Tamil Nadu: a community-based cross-sectional study - Kulothungan, Karthikeyan; M., Tamilarasan; Rock Britto, D.; SriRanganathan, T.; SriAndaal, V. (International Journal Of Community Medicine And Public Health, 2018)
Background: Aging is a complex process that occurs by an increase in cellular injury that occurs at the biological level over a period. These injuries lead to decline in the capacity of the individual due to a gradual reduction in physiological reserves. The objectives of the study were to estimate the prevalence of common physical health problems and to assess the effect of aging influencing them among the geriatric population. Methods: A community-based cross-sectional study was conducted in 9 randomly selected wards among 400 elderly subjects of aged 60 years or above by using probability proportionate to size (PPS) sampling method in urban residents of Perambalur municipality, Perambalur district, Tamil Nadu using semi structured questionnaire. Data entry and analysis was done using SPSS version 16.0. Results: The mean age of the study population was 71.28±7.85. Three-fourths of the study subjects were not doing any work and the majority of them (80%) was living with family members and looked after by their family members (88%). In our study, it was found that the most prevalent common physical health problem among the geriatric population was dental diseases (85.75%) followed by diseases of the locomotor system (81.75%). Almost 99% of the elderly have at least a single system involvement. Conclusions: The preventive and rehabilitative services planned by the government have to be elder-friendly. To improve the health status of the elderly various health schemes, policies and programs can be designed based on the study findings.